Optimization of therapy of type 2 diabetes mellitus with the oral hypoglycemic agent glimepiride - Tatiana Ivanovna Romantsova; Nadezhda Viktorovna Maksimova (Сахарный диабет)
Type 2 diabetes is believed to develop as a result of lowered insulin secretion and insulin resistance leading to hyperglycemia. Sulfonylureas stimulateinsulin secretion and thereby decrease blood glucose level which accounts for their wide application in the treatment of diabetes. However, manyagents of this class produce side effects (increased body mass, hypoglycemia, resistance to therapy, etc.) attributable to excess stimulation of insulinsecretion. Glimepiride is as efficient as traditionally used sulfonylureas but causes a smaller rise in insulin secretion. Sulfonylurea receptors showlower affinity for glimepiride than for glibenclamide. Formation and dissociation of glimepiride-receptor complexes occur faster than those of glibenclamide-receptor complexes. In addition, therapeutic effect of glimepiride was shown to be associated with improved insulin sensitivity. It is concludedthat glimepiride is an efficacious agent for the treatment of type 2 diabetes.